The Influence of Knowledge Level on Adolescents' Interest in Practicing Ayurvedic Yoga to Alleviate Premenstrual Syndrome (PMS) Symptoms - Nahdiyatul Mukaromah; Muslimah, Rifa'at Hanifa (Rifa'Institute, 2024)
Abstract Introduction: Premenstrual Syndrome (PMS) is a condition characterized by behavioral and emotional changes that occur prior to menstruation. Common symptoms include altered appetite, weight gain, abdominal pain, back pain, lower back pain, headaches, breast tenderness and swelling, nausea, constipation, restlessness, irritability, anger, fatigue, and mood swings. One non-pharmacological approach to managing PMS symptoms is Ayurvedic yoga therapy. Understanding the relationship between adolescents' knowledge of Ayurvedic yoga and their interest in practicing it can provide valuable insights, particularly in promoting natural alternatives for PMS management. Aim: This study aims to examine whether there is a significant relationship between knowledge about Ayurvedic yoga and the interest in practicing it among adolescents experiencing PMS. Method: This research employs a quantitative approach using a cross-sectional design. The study population consisted of female adolescents aged 15 to 19 years. Participants were selected through purposive sampling. Data were collected using questionnaires assessing knowledge of and interest in Ayurvedic yoga. Results: The analysis was conducted using the Mann-Whitney test, resulting in a p-value of 0.00 (< 0.05), indicating a statistically significant relationship between knowledge and interest in practicing Ayurvedic yoga among adolescents with PMS. Conclusion: Improving knowledge about Ayurvedic yoga has the potential to enhance adolescents' interest in adopting it as a strategy for managing PMS symptoms. Therefore, appropriate and informative education on the benefits and techniques of Ayurvedic yoga is essential